The Connection between the Endometrial Thickness and the Risk of Endometrial Malignancy in Postmenopausal Women - Tofiloska, Valentina; Velikj Stefanovska, Vesna; Dimitrov, Goran (Scientific Foundation SPIROSKI, 2019)
Background: Postmenopausis is a period that starts one year after the last menstruation. Late menopause, after 70 years, is called senile. Aim: To examine the correlation between endometrial thickness and the risk of endometrial malignancy in postmenopausal. Material and methods: Prospective clinical study involving 120 postmenopausal patients treated at the University Clinic for Gynecology and Obstetrics - Skopje, divided into two groups: control and examination. The control group included 40 postmenopausal patients, hospitalised and operated due to urogenital pathology. The examined group consisted of 80 patients divided into three subgroups according to the ultrasound verified thickness of the endometrium: from 5-8 mm; > 8-11 mm and above 11 mm. A detailed history and intervention were taken in the patients from both groups, and the material was sent for histopathological analysis to determine eventual malignancy. Results: The probability of endometrial malignancy significantly increased by 1.012 times in the group with a thickness of the endometrium from 5-8 mm, 1.769 times in the endometrial thickness group > 8-11 mm and 4.737-fold in the group over 11 mm compared to the control group. Conclusion: In postmenopausal patients, the likelihood of endometrial cancer significantly increases with the thickness of the endometrium.